Kompleksitas Persoalan Pemenuhan Hak Penyandang Disabilitas Di Pengadilan Negeri Pekanbaru - July Wiarti (Jurnal Hukum IUS QUIA IUSTUM, 2020)
The population of persons with disabilities in Indonesia that continues to increase if not handled properly has the potential to cause discrimination even though there are several laws and regulations on persons with disabilities. Moreover, the social paradigm towards persons with disabilities is often likened to the person's medical inability, hence disability is considered as a sick person who always needs assistance and unable to receive education, let alone work like humans in general. It is not surprising if to this day, there are still many obstacles experienced by persons with disabilities in getting public services. Of the many obstacles that exist, the most common ones encountered, even though its existence is very important in human life is the obstacle in getting access to justice. Admittedly, persons with disabilities still often face discrimination when dealing with the law in court. Therefore, in this study the author analyzed the legal protection of persons with disabilities by dealing with the law and the empirical conditions of fulfilling their rights in Pekanbaru District Court. This is a form of juridical-normative research. The results of the study conclud that the state is quite appropriately protecting the rights of persons with disabilities through the legislation. However, from the implementation aspect in Pekanbaru District Court, there are still obstacles in physical facilities, regulation, and knowledge